Integrated Science New Approaches to Education - Brint, Michael E.; Marcey, David J.; Shaw, Michael C.; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
With the global challenges that face us and our environment, there is a growing sense among leaders in science, public policy, business, and education that we need new, more integrative approaches to science. In turn, these interdisciplinary and multidisciplinary approaches to solving problems at the frontiers of science demand responses and reformations at the institutional level. Integrated Sciences:New Approaches to Education, a "virtual roundtable" on the topic of integrative science,creates a symphony of voices addressing the pluralistic nature of approaches to recasting science research and education. The "participants" come from different perspectives and experiences, and include Nobel laureates, university presidents, serious scholars, and distinguished scientists. Although their comments, talks, articles, and interviews on this subject may have taken place at different times and in widely different venues, they have been organized into a coherent ensemble of conversations about the necessity, promises, challenges, and implementation of integrative approaches to scientific research and education. This book will be helpful to a wide range of scientists, educators, and university and college administrators facing the exciting, if daunting, hurdles involved in integrative reform.
Keywords: EDUCATION; MEDICINE; LIFE SCIENCES; SCIENCE -- STUDY AND TEACHING; EDUCATION; SCIENCE EDUCATION; POPULAR SCIENCE IN MEDICINE AND HEALTH; LIFE SCIENCES, GENERAL; BIOMEDICINE GENERAL; EDUCATIONAL TECHNOLOGY